Santriwati's role in preventing digital violence against women: The KUPI trilogy approach - Mutholingah, Siti; Januari, Anas Tania; Masuwd, Mowafg (UIN Ar-Raniry Banda Aceh, 2025)
Violence against women in the digital space was common, including digital harassment, defamation on social media, and other forms. Santriwati, as part of the women's community in pesantren, had a crucial role in addressing this issue. This study aims to analyze the role of female students in overcoming digital-based violence against women using the KUPI (Kongres Ulama Perempuan Indonesia) trilogy approach at the Al-Hikam Pesantren. This study used a qualitative approach with a case study research type. Data collection used participatory observation, interviews, and documentation. For the informant, the female guardians, the female student organization administrators, and several female students, because they were most knowledgeable about the research focus. The documents obtained included the female student organization's work program for preventing digital-based violence against women. The results, the santriwati's role in overcoming violence against women using the KUPI trilogy approach, namely santriwati as agents of pioneering good content in the digital world (ma'ruf), santriwati together with santri act as partners in the digital world (mubadalah), and santriwati as drivers of social justice in the digital world (keadilan hakiki). The novelty in the study was the concept of